Heterosis for grain yield and its components in topcross hybrids of maize - B. Alhessein, Mohammedein; S. Ibrahim, Abu Elhassan; S. Ali, Eltahir (المجلة الزراعية; مجلد 10 عدد 1 (2012), 2022)
Development of high yielding hybrids with high vigor is the ultimate objective of maize breeding and the success depends largely on the identification of the best parents to ensure maximum heterosis for hybrid production. This study was conducted to estimate genetic variability and heterosis of grain yield and yield components  of seven local inbred lines and four introduced open pollinated varieties of maize ( Zea mays L.) across  two irrigated locations (Medani and Matuq) in 2008. The experiment was arranged in a randomized complete block design with three replicates. The traits measured were days to 50% tassel, plant height, ear length, ear diameter, hundred kernels weight and grain yield. The crosses showed high genetic variability and tall plants than their parents which suggested some degree of hybrid vigor. The tallest hybrids across locations were T3 x L5 and T4 x L3. This indicates that the crosses were late maturing than their parents. The highest yielding hybrids had long ears and better shape, e.g., T2 x L1 and T1 x L7.The top five ranking crosses for grain yield across locations were T2 x L7 (3.45 t/ha), T1 x L2 (3.44 t/ha), T2 x LI (3.32 t/ha), T4 x L4 (3.30 t/ha) and T1 x L1 (3.13 t/ha). The highest percentage of mid parent heterosis for grain yield in Medani, was given by T3 x L3 and T4x L4; in Matuq, by T1 x L5, T4 x L5 and T4 x L6 and across sites by T1 x L2 (59%), T3 x l2 (45%) and T3 x L6 (50%). These crosses can be recommended for future testing in multilocations trials for commercial utilization.    تحسين صفات الإنتاجية لمحصول الذرة الشامية هي الغاية المنشودة من خلال التربية لإنتاج الهجن والتي تعتمد على تحديد أفضل الآباء وأكثرها قوة لإنتاج الهجين. لذا أجريت هذه الدراسة لتقدير التباين الوراثي و قوة الهجين لأربعة سلالات تربية داخلية وسبعة أصناف مستقدمة مفتوحة التلقيح من الذرة الشامية ( Zea mays L.) تحت ظروف ري مستدام، موسم 2008 .استخدم تصميم القطاعات العشوائية الكاملة بثلاثة مكررات لتنفيذ التجربة. الصفات التي تمت دراستها شملت 50% لعدد أيام الإزهار المذكر ، طول النبات، طول الكوز، حجم الكوز، وزن المائة حبة وإنتاجية الحبوب.أظهرت النتائج فروق معنوية لكل  الصفات في الموقعين وأكثر تباينا وراثياً في طول النبات وفترة النضج.  وجد أن الهجن متأخرة في الأزهار وفترة النضج مقارنة بالآباء. أما  طول وحجم صفات القندول فقد وجد أن لها أهمية كبرى في زيادة  الإنتاجية وأفضل الهجن هي T1 x L7 و T2 x L1  .أعلى الهجن إنتاجية هى 3.45) T2 x L7طن/هكتار) و 3.44) T1 x L2 طن/هكتار)  وT2 x LI(3.32 طن/هكتار) و T4 x L4( 3.30طن/هكتار) و T1 x L1(3.13طن/هكتار ). الهجن التي أظهرت أعلى قوة هجين في مدني هيT3 x L3 و   T4x L4وفي معتوق للهجن T1 x L5, T4 x L5 و T4 x L6 وعبر الموقعين هى    (59%)T1 x L2و (45%)T3 Xl2   و (50%)T3 x L6. ومن خلال هذه الدراسة نوصى باستخدام هذه الهجن بعد إجراء بعض الاختبارات الخاصة بالإنتاجية في مواقع ومواسم مختلفة.